Xanthine dehydrogenase‐1 silencing in Aedes aegypti mosquitoes promotes a blood feeding–induced adulticidal activity. Issue 6 (8th February 2017) - Isoe, Jun; Petchampai, Natthida; Isoe, Yurika E.; Co, Katrina; Mazzalupo, Stacy; Scaraffia, Patricia Y.
ABSTRACT: Aedes aegypti has 2 genes encoding xanthine dehydrogenase (XDH). We analyzed XDH1 and XDH2 gene expression by real‐time quantitative PCR in tissues from sugar‐ and blood‐fed females. Differential XDH1 and XDH2 gene expression was observed in tissues dissected throughout a time course. We next exposed females to blood meals supplemented with allopurinol, a well‐characterized XDH inhibitor. We also tested the effects of injecting double‐stranded RNA (dsRNA) against XDH1, XDH2, or both. Disruption of XDH by allopurinol or XDH1 by RNA interference significantly affected mosquito survival, causing a disruption in blood digestion, excretion, oviposition, and reproduction. XDH1‐deficient mosquitoes showed a persistence of serine proteases in the midgut at 48 h after blood feeding and a reduction in the uptake of vitellogenin by the ovaries. Surprisingly, analysis of the fat body from dsRNA‐XDH1‐injected mosquitoes fell into 2 groups: one group was characterized by a reduction of the XDH1 transcript, whereas the other group was characterized by an up‐regulation of several transcripts, including XDH1, glutamine synthetase, alanine aminotransferase, catalase, superoxide dismutase, ornithine decarboxylase, glutamate receptor, and ammonia transporter. Our data demonstrate that XDH1 plays an essential role and that XDH1 has the potential to be used as a metabolic target for Ae. aegypti vector control.—Isoe, J., Petchampai, N., Isoe, Y. E., Co, K., Mazzalupo, S., Scaraffia, P. Y. Xanthine dehydrogenase‐1 silencing in Aedes aegypti mosquitoes promotes a blood feeding–induced adulticidal activity. FASEB J. 31, 2276–2286 (2017). www.fasebj.org